Masa Jabatan Kepala Desa: Suatu Wacana - Tjoe Kang Long; Widyawati Boediningsih (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
It is generally known that the duration of the Village Head's leadership period generally only lasts for 6 years based on Law Number 6 of 2014 concerning Villages. However, lately there has been a viral case, in an effort to extend the tenure of the village head from six years to nine years, the village heads asked the Indonesian Parliament to revise this provision. Members of the Village Head who are members of the Papdesi (All-Indonesia Association of Village Government Apparatuses) flocked to Jakarta, to be precise in front of the DPR Building to hold a demonstration demanding an extension of their term of office. Provisions regarding the tenure of the Village Head are contained in Article 39 of the Village Law, which states that (1) The Village Head serves for 6 (six) years from the date of inauguration; (2) The Village Head in accordance with paragraph (1) may serve a maximum of 3 (three) consecutive or non-consecutive terms of office.